Learning Flow, Critical Thinking Disposition, and Communication Competency of Nursing College Students - Yoon, Misun; Yim , Soyoun; Kim, Heejeong (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: The purpose of this research is to investigate the relationships of learning flow, critical thinking disposition, and communication competency among nursing college students. Methods/Statistical analysis: For data collection self-reported questionnaires were used to 132 senior nursing students in nursing college in South Korea. Data were collected from September 2 to 20, 2018. Data were analyzed by descriptive statistics for general characteristics. Correlation coefficient was used to explore the relations of the learning flow, critical thinking disposition, and communication competency among nursing college students. Results: In this study, the mean of learning flow, critical thinking disposition, and communication competency were 2.69±0.52, 96.16±14.13, 3.36±0.44, respectively. The learning flow showed statistically significant relationships with critical thinking disposition(r=-.496, p<.001) and communication competency (r=.473, p<.001). The critical thinking disposition showed negative correlation with communication competency(r=-.819, p<.001). Improvements/Applications: It is needed to figure out other variables related with learning flow. And various teaching methods and environment should be considered to enhance learning flow of nursing college students.